Graphene-beaded carbon nanofibers with incorporated Ni nanoparticles as efficient counter-electrode for dye-sensitized solar cells. (April 2016) - Zhou, Zhengping; Sigdel, Sudhan; Gong, Jiawei; Vaagensmith, Bjorn; Elbohy, Hytham; Yang, Huojun; Krishnan, Sumathy; Wu, Xiang-Fa; Qiao, Qiquan
Abstract: A novel porous three dimensional (3D) hierarchical graphene-beaded carbon nanofibers with incorporated Ni nanoparticles (G/CNFs–Ni) were used for the first time as cost-effective counter-electrode for dye-sensitized solar cells (DSCs). G/CNFs–Ni was synthesized by electrospinning G/PAN/Ni(AcAc)2 precursor nanofibers, followed by carbonization and activation. The introduction of graphene nanosheets and Ni nanoparticles in CNF networks significantly increased the cells' stability and decreased the charge-transfer resistance at the interface between electrolyte and counter-electrode, leading to the high electrocatalytic activity/efficiency for triiodide reduction. The G/CNFs–Ni composite counter-electrodes possessed larger capacitance than that of Pt counter-electrodes due to larger specific surface area, leading to significantly higher electrocatalytic activity/efficiency for triiodide reduction at the interface between electrolyte and counter-electrode. The dye-sensitized solar cells (DSCs) fabricated using G/CNFs–Ni composite as counter-electrodes were tested at 100 mW/cm 2 AM 1.5 illumination. The G/CNFs–Ni composite exhibited an overall power conversion efficiency of 7.14% as compared to 7.59% for reference platinum (Pt) counter-electrodes. Graphical abstract: 3D hierarchical graphene-beaded carbon nanofibers with incorporated Ni nanoparticles (G/CNFs–Ni) were used as counter-electrode for dye-sensitized solar cells. Highlights: 3D hierarchical G/CNFs–Ni was developed as a novel counter-electrode nanomaterial for efficient DSCs. G/CNFs–Ni was synthesized by electrospinning G/PAN/Ni(AcAc)2 precursor nanofibers, followed by carbonization and activation. Graphene and Ni in CNF networks significantly increased the cells' stability and decreased the charge-transfer resistance. G/CNFs–Ni Possessed larger capacitance than that of Pt due to larger specific surface area, leading to higher efficiency.